2012
DOI: 10.4025/actascianimsci.v34i3.10577
|View full text |Cite
|
Sign up to set email alerts
|

Indigestible cellulose and lignin in determining feces production and apparent digestibility in horses

Abstract: 0.05) was 101%. Nutrient digestibility coefficient (p > 0.05) estimates were adequately predicted by iCEL and iLIG, obtained in situ or in vivo, with average values of 52.63, 54.17, 64.90, 43.73 and 98.28% for dry matter, organic matter, crude protein, neutral detergent fiber and starch, respectively. It can be concluded that iCEL and iLIG may be obtained in vivo by MNB in horses consuming a forage-concentrate diet, to predict nutrient digestibility coefficients.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Despite the presence of multiple CEs (Fig. 4 ), the lack of auxiliary-active enzymes (AAs) indicates a low capacity of the capybara microbiota to perform plant biomass delignification, as also observed for other monogastric herbivores 32 , 33 . As a mechanism to cope with lignin-rich diets, these animals may employ cecotrophy to enhance digestibility and nutrient uptake.…”
Section: Resultsmentioning
confidence: 64%
“…Despite the presence of multiple CEs (Fig. 4 ), the lack of auxiliary-active enzymes (AAs) indicates a low capacity of the capybara microbiota to perform plant biomass delignification, as also observed for other monogastric herbivores 32 , 33 . As a mechanism to cope with lignin-rich diets, these animals may employ cecotrophy to enhance digestibility and nutrient uptake.…”
Section: Resultsmentioning
confidence: 64%
“…Digestion of a fraction of lignin by microbial activity, source of plant lignin and content of lignin in the diet might be the factors responsible for incomplete faecal recoveries (Sales 2012). Assuming the possibility of partial digestibility of lignin, Oliveira et al (2012) suggested using only the indigestible fraction of lignin as a marker in digestibility studies. Peiretti et al (2003) and Bergero et al (2005) found out that a higher level of ADL in feed rations can lead to more precise determination when studying digestibility of nutrients by using lignin as a marker in horses.…”
Section: Resultsmentioning
confidence: 99%
“…Deer and horses eat multiple plants that grow in their environment. A part of the plants ingested as food is absorbed through the metabolism of the herbivore, and another part is excreted as droppings [15]. Additionally, intestinal bacteria may be responsible for digesting cellulose and lignin contained in plants that are di cult to digest by the herbivore itself [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…A part of the plants ingested as food is absorbed through the metabolism of the herbivore, and another part is excreted as droppings [15]. Additionally, intestinal bacteria may be responsible for digesting cellulose and lignin contained in plants that are di cult to digest by the herbivore itself [15,16]. In this way, horses and deer commonly feed on multiple species of herbaceous plants, and the digestion of cellulose depends in part on the intestinal ora.…”
Section: Discussionmentioning
confidence: 99%